THE PROBLEM OF RESERVING TRADITIONS OF CALLIGRAPHY IN THE EAST AND THE WEST - E. M. Kulanina (Концепт: философия, религия, культура, 2017)
The art of calligraphy is based on cultural traditions, culture, philosophy, education, science, and religion. In this article the author considers calligraphy from the point of view of traditional and modern approaches to social and cultural needs of a person in modern conditions of computerization, and the consequences of the use of calligraphy after the invention of the printing press throughout the historical development. The author analyses different approaches to manners of teaching and practical application of calligraphy, and also views key points of the dialogue between East and West on the art of calligraphy in its traditional and cultural development. The article considers recent studies of modern rethinking of values and the art traditions of the past, present and future, also of a significant impact of modern individual experience, on perception of the world and people’s behaviour. The article suggests severalmodern methods of studying calligraphy, its development and traditions in different cultures, and how it could help to resolve current sequence of dysgraphia problems; methods which also could create specific calligraphy skills of students and organize their personality, which depends on many factors such as the degree of involvement in the cultural development of the country, on its ability to retain, supply and properly orientate oneself through the world’s cultural diversity of historically created traditions. With the help of an example of interaction and cooperation between cultures which are based on the features of distinctive approaches, taking into consideration the inherent historical development, a dynamic image of modern life, a partial modification of the traditional value systems and the appearance of new ones, the author considers the main aspect of the cultural dialogue between East and West about approaches to calligraphy - are these harmonically balanced methods of new trends and tendencies of art into the existing system which has been already developed. Thus, the article is an updated search for new understandings of cultural reality, causing the formation of the personality of each person.